2016
DOI: 10.1016/j.cbpb.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and fatty acid/alcohol compositions of the subarctic copepods Neocalanus cristatus and Eucalanus bungii from various depths in the Oyashio region, western North Pacific

Abstract: Lipids of Neocalanus cristatus and Eucalanus bungii (C3 to adults), collected in March, May, and December from various depths (0-2000 m) were studied in the Oyashio region, western North Pacific. Total lipid and wax ester contents of younger N. cristatus stages increased during the development, being higher in May than in March and December. Major fatty acids of younger N. cristatus were 16:0, 20:5(n−3), and 22:6(n−3) and the dominant alcohols were 16:0, 16:1(n − 7), 20:1(n − 9)/(n −11) and 22:1(n −11). The en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…In most taxa, we did not separate life stages, and that potentially confounded seasonal differences as there may be dietary shifts, e.g., increased carnivory with age. Yamada et al (2016) found differences in both lipid content and composition among life stages and seasons of copepods in the western North Pacific, and several studies in polar regions have found strong seasonality in lipids (Kattner et al 1994;Mayzaud et al 2011). However, consistent with our results, Costalago et al (2020) found that season and region had statistically significant but minor effects on zooplankton fatty acid composition in the northern Salish Sea.…”
Section: Discussionsupporting
confidence: 90%
“…In most taxa, we did not separate life stages, and that potentially confounded seasonal differences as there may be dietary shifts, e.g., increased carnivory with age. Yamada et al (2016) found differences in both lipid content and composition among life stages and seasons of copepods in the western North Pacific, and several studies in polar regions have found strong seasonality in lipids (Kattner et al 1994;Mayzaud et al 2011). However, consistent with our results, Costalago et al (2020) found that season and region had statistically significant but minor effects on zooplankton fatty acid composition in the northern Salish Sea.…”
Section: Discussionsupporting
confidence: 90%
“…Concurrently, this species had one of the lowest δ 15 N values (8.55‰). These results suggest that this species had a diet dominated by phytoplankton, unlike many copepod species that are omnivorous, and may thus be an important, albeit of relatively poor nutritional quality, link between primary producers and the fish that consume these copepods 52 .…”
Section: Discussionmentioning
confidence: 88%
“…southern and carnivorous species) which may potentially decrease the efficiency of biomass transfer due to higher metabolic rate requirements that lead to higher respiration losses (Palomares and Pauly, 1998;Heilmayer et al, 2004;Pörtner et al, 2012;Barneche and Allen, 2018). Additionally, these southern species may be considered a less desirable prey source as they are usually less lipid-rich than subarctic and boreal-shelf counterparts (Tsuda et al, 2004;Yamada et al, 2016). Therefore, increases in the abundance of non-endemic copepod and gelatinous zooplankton species may increase the functional diversity of the community while simultaneously decreasing the efficiency with which energy is transferred.…”
Section: Implications For Higher Trophic Levelsmentioning
confidence: 99%
“…This is particularly important when comparing southern versus boreal-shelf and subarctic copepod group species as well as crustacean versus gelatinous zooplankton. Southern copepod species have been considered less lipid-rich than their northern subarctic NE Pacific counterparts (Tsuda et al, 2004;Yamada et al, 2016). A recent study has highlighted that many gelatinous zooplankton species do not have the same weight-specific energy content when compared to crustacean zooplankton species, with the exception of some Gastropoda and Tunicata species (Lüskow et al, 2021).…”
Section: Future Applicationsmentioning
confidence: 99%